The macroinvertebrate fauna of maintained and abandoned beaver dams - Sara Schloemer; Thomas Hörren; Armin W. Lorenz; Daniel Hering (Hydrobiologia, 2023)
Beavers and their dams, once common in small streams throughout Eurasia and North America, are returning to their original range. Beaver dams are special habitats in the aquatic-terrestrial interface, but their macroinvertebrate fauna is hardly known. This study aims to qualify and quantify the invertebrate fauna of beaver dams, taking into account the maintenance status of the dams. Nine different areas covering the top, middle and base zones of eight maintained and eight abandoned beaver dams were sampled using a specially designed suction device. The invertebrate community of beaver dams proved to be diverse and predominantly rheophilic. Community composition reflects higher flow velocities in streamside habitats; this gradient is more pronounced in maintained than in abandoned dams. Shredders are the most abundant feeding type, but they are less frequent in streamside habitats, in particular in those of maintained dams, where passive filter feeders prevail. Terrestrial/Semiaquatic taxa colonising hygropetric areas were found in streamside habitats especially of abandoned dams. Our results underline that beaver dams provide a wide variety of environmental conditions and habitat types, which enhance biodiversity in small streams and their floodplains. Beaver dams in riverine landscapes should therefore be much more valued in floodplain conservation and management.